Technology of Animal Feed Processing (Fermentation and Silage) in Bilah Hulu Village, Labuhan Batu Regency - Putra, Andhika; D, Ismail; Lubis, Najla (Journal of Saintech Transfer, 2018)
The specific target in this activity was to introduce fermentation and silage methodology to improve the quality of animal feed to Mekar Baru stock farmers cooperatives in Labuhan Batu Regency. Seminars and discussions were conducted as parts of the community service which then followed up by direct practice about animal feed fermentation and silage. The results of the mentioned activities included seminars, discussion, and fodder. In conclusion, the technology of animal feed processing is in a high favorand needed by people in the village, especially beef cattle farmers whose livestock was only given green animal feed all this time.